Geopolitical Influence and Trade between Bangladesh and India (Bangladesh Journal of Public Administration, 2020)
The aim of this study is to explore the geopolitical dynamics and trade relationship between India and Bangladesh. The content analysis method has been followed to conduct this study. Secondary data has been used to substantiate the argument. The study reveals that geopolitical aspects of India affect the features of the Bangladesh economy. The study also explores that one of the main weaknesses of Bangladesh is its inability to diversify export which make Bangladesh susceptible to accept dominancy and unequal trade relationship to a neighboring country. This study is formed to improvise trade operations considering all areas of development between India and Bangladesh to solidify the trade relation. Keywords: Geopolitics, India, Bangladesh, international trade, strategic relationship, diplomacy